Factor Analysis of Competency of Computer Teacher at Vocational Certificate Level - Punnee Leekitchwatana; Paitoon Pimdee; Sangutai Moto (My University, 2013)
The research objectives were to analysis the factor and construct the questionnaire on competency of computer teacher at vocational certificate level of educational institute under Office of Vocational Education Commission (OVEC). The descriptive research and structural relationship model were used for the study. Sample groups comprised of 1) 90 experts and 2) 200 educational institutes under OVEC. Research instruments were questionnaires on competency of computer teacher at vocational certificate level for: 1) experts and 2) educational institutes. Data analysis were conducted with: 1) Exploratory factor analysis by using SPSS for Windows for data from experts, 2) The second order confirmatory factor analysis with LISREL 8.72 program and Cronbach’s α formula for data from educational institutes. Research results revealed that competency of computer teacher at vocational certificate level composed of 12 components from 62 variables covered 3 domains of knowledge, skill, and affection. Those 12 components were general knowledge about education, knowledge about curriculum, knowledge about teaching, knowledge about e-Learning and e-Media, knowledge about IT support, knowledge about computer use, teaching skill, skill about e-Learning and e-Media, skill about IT support, skill for using computer, supportive affection to be a teacher and affection in IT. The questionnaire on competency of computer teacher had good quality with good construct validity and high reliability in 2 dimensions of intent and actual competencies.
Keywords: Certificate; Exploratory factor analysis; Affection; LISREL; Educational Systems and Policies